Undesired effects of relief systems concerns mitigations. Issue 3 (16th January 2021) - Wakil, Waheed
Abstract: Process changes and lack of proper relief systems documentation are some reasons why relief systems may need to be revalidated during the life of a facility. When revalidating relief systems, concerns may be identified such as improper relief device size, high inlet or outlet pressure drop, or unprotected equipment. The solution is often more complicated than you may think. Without expert knowledge of the various recognized and generally accepted good engineering practices (RAGAGEP) related to relief systems, a seemingly simple fix may result in undesired consequences that may lead to a more dangerous situation than the previous design. This paper goes into some examples of undesired effects of relief systems changes, including negative effects on upstream or downstream equipment, effects of changes in relief device set pressure, effects of changes in relief device type, and effects of piping changes.